Comparative effect of papaya (Carica papaya) leaves’ extract and Toltrazuril on growth performance, hematological parameter, and protozoal load in Sonali chickens infected by mixed Eimeria spp. (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Anticoccidial drugs may lead to the development of drug resistance and drug residues. Herbal extracts could be an attractive alternative. This research was undertaken to evaluate the anticoccidial outcome of Carica papaya compared with the anticoccidial drug (Toltazuril) in Sonali chickens.  Materials and Methods: A total of 80 Sonali chickens were evenly and equally allocated into four groups, namely T1 (non-infected control), T2 (infected control), T3 (treated with C. papaya), and T4 (treated with Toltrazuril). All groups were experimentally infected with oocysts of mixed Eimeria spp. orally except T1, and the mixed Eimeria spp. oocyst load (OL), body weight (BW) gain, and hematological parameters were calculated.  Results: In the findings, the highest OL reduction rate in T4 was 100%, while the T3 was 83.44%. Nevertheless, BW differed significantly (p < 0.01) among the different groups, while the daily BW gain was higher in T3 amounting to 8.10 gm. In the case of hematological parameter, total erythrocyte count (TEC), hemoglobin (Hb), packed cell volume (PCV), and erythrocyte sedimentation rate in different groups were almost the same and were also statistically insignificant (p > 0.05) barring total leukocyte count resulting as significant (p < 0.05) at day 30. Additionally, the results of Pearson’s correlation in T3 at day 30 indicated a strong significant (p < 0.01) negative correlation between OL and BW (r = −0.780) with the following regression equation: y = −0.16*x + 433.665. Moreover, the correlation of TEC, PCV, and Hb with OL was significantly (p < 0.01) negative, r = −0.786, r = −0.752 and r = −0.633, where the regression equations were y = −0.03*x + 4.51, y = −0.03*x + 27.42, and y = −0.04*x + 11.40, respectively.  Conclusion: Long-term use of C. papaya leaves’ extracts effectively controls coccidiosis in Sonali chickens and can act as an effective growth promoter.J. Adv. Vet. Anim. Res., 8(1): 91-100, Mar 2021http://doi.org/10.5455/javar.2021.h490